Psychosocial functioning of pupils of the ballet studio of senior preschool age - Kateryna Berezina (Kharkiv State Academy of Physical Culture, 2021)
Purpose:identification of the psychosocial development features of senior preschool pupils of a private ballet studio in Kharkov. Material and methods: the study involved 20 pupils of the Kharkov ballet studio at the age of 5 to 7 years, who have been practicing ballet from 10 months to 2 years. To obtain the results, we used the methodology of M. Jellinek and M. Murphy «List of childhood symptoms» PSC and Y-PSC in the Ukrainian adaptation of the «CC list of childhood symptoms» PSC-UKR and Y-PSC-UKR (OL Lutsenko, D.V. Shtrygol, N.G. Mikhanovskaya), namely the PSC version, which is filled in by the child's parents. Results: the results of our research showed that, according to the assessment received from their parents, 45% of the pupils of the ballet studio have some psychosocial problems. At the same time, 25% have such problems on the scale of «internalization», and another 20% - on the scale of «externalization». Among 25% of the respondents who had some problems on the internalization scale, the most common answers were that the child gets tired quickly, is afraid of new situations, wants to be with his parents more than usual, feels bad and has less fun. Among the 20% of respondents who had some problems on the scale of externalization, the most common answers were that the child is restless, cannot sit still, is less interested in school (in our case, in ballet classes), acts «like an instinct», is easily distracted , flies too much in the clouds, doesn't follow the rules. Conclusions: most of the pupils of the ballet studio have harmonious psychosocial development as assessed by their parents. Therefore, it can be assumed that ballet classes have a positive effect on the psychosocial development of older preschoolers.